Fungal Infections, Treatment and Antifungal Resistance: The Sub-Saharan African Context - Emily Boakye-Yiadom; Alex Odoom; Abdul-Halim Osman; Onyansaniba K. Ntim; Fleischer C. N. Kotey; Bright K. Ocansey; Eric S. Donkor (Therapeutic Advances in Infectious Disease)
Fungal pathogens cause a wide range of infections in humans, from superficial to disfiguring, allergic syndromes, and life-threatening invasive infections, affecting over a billion individuals globally. With an estimated 1.5 million deaths annually attributable to them, fungal pathogens are a major cause of mortality in humans, especially people with underlying immunosuppression. The continuous increase in the population of individuals at risk of fungal infections in sub-Saharan Africa, such as HIV patients, tuberculosis patients, intensive care patients, patients with haematological malignancies, transplant (haematopoietic stem cell and organ) recipients and the growing global threat of multidrug-resistant fungal strains, raise the need for an appreciation of the region’s perspective on antifungal usage and resistance. In addition, the unavailability of recently introduced novel antifungal drugs in sub-Saharan Africa further calls for regular evaluation of resistance to antifungal agents in these settings. This is critical for ensuring appropriate and optimal use of the limited available arsenal to minimise antifungal resistance. This review, therefore, elaborates on the multifaceted nature of fungal resistance to the available antifungal drugs on the market and further provides insights into the prevalence of fungal infections and the use of antifungal agents in sub-Saharan Africa.